Detection of IR and sub/THz radiation using MCT thin layer structures: design of the chip, optical elements and antenna pattern - Sizov, F.F.; Tsybrii, Z.F.; Zabudsky, V.V.; Sakhno, M.V.; Shevchik-Shekera, A.V.; Dukhnin, S.Ye.; Golenkov, A.G.; Dieguez, E.; Dvoretsky, S.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Two-color un-cooled narrow-gap MCT (mercury-cadmium-telluride) semiconductor thin layers, grown by liquid phase epitaxy or molecular beam epitaxy methods on high resistivity CdZnTe or GaAs substrates, with bow-type antennas were considered both as sub-terahertz direct detection bolometers and 3...10-micrometer infrared photoconductors. Optical system with aspheric THz lenses were designed and manufactured. An antenna pattern of structures on the thick substrate was discussed, and sensitivity of detector in both IR and sub-THz regions was measured.